119k views
1 vote
-3(m + -8) + -12 = -3
show work step by step.
solve for m

2 Answers

4 votes

Question: Answer: m = 5

-3(m + -8) + -12 = -3 solve for m

Step-by-step

-3(m + -8) + -12 = -3

Add 12 to both sides

-3(m + -8) + - 12 = -3

+12 +12

-3 ( m - 8 ) = 9

Divide both sides by -3

-3 ( m - 8 ) = 9

-3 -3

m - 8 = -3

add 8 to both sides

m - 8 = -3

+ 8 +8

m = 5

User Swyx
by
5.8k points
4 votes

Answer:

m=-11

Explanation:

Isolate the variable by dividing each side by factors that don't contain the variable

hope this helped :))

User Franiis
by
5.4k points